A Study on Hand Grip Force for Push Activity at Aerospace Industry - Kamat, S.R.; Ani, M.F.; Kushairi, S.; Ghazali, A.; Zulkeflle, S.N.; Husin, K. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Grip strength is the force applied by the hand to push objects and is a specific part of hand strength. It is generally considered that all aspects of the hand must be exercised to produce a healthy and strong grip. The purpose of this study is to analyze the hand grip force that causes discomfort for push activity among the workers in the aerospace industry while workers performing their task. Data were collected by using observation, interview, questionnaires, and Tekscan grip system tools were used to evaluate hand grip pressure force of the workers. Findings show that the individual factors such as age and body size have affected the hand pressure grip force. Besides, the study shows that the hand grip pressure forces when pushing the mold with the right hand are higher than left hand. At the end of this study, the authors concluded that high grip forces will lead to a risk factor for the development of MSDs.